DEKONTRUKSI EPISTIMOLOGI ILMU-ILMU SOSIAL: SEBUAH KENISCAYAAN - Suryadi, Suryadi (Fakultas Ilmu Politik dan Ilmu Sosial, Universitas Brawijaya, 2010)
Modern science in the world is built with Atheism view of live. As modern science impact, actually social science fails to finish the human being problem, and fails to know the human it self. For this, insisting on epistemologycal decontruction, if us not wish be hard situation. As the answer of this challenge, the atheism view of live must be show again. Learn from west Asia in middle ages, apocalipse should be made premis which basically all opinion and elementary of validasi result of research. With this method, there is no dissociation for what referred science and religion. Â Key Words: deconstruction, epistemology, science.